The Trans-Tasman Therapeutic Products Authority: Potential AUSFTA Impacts on Safety and Cost-Effectiveness Regulation for Medicines and Medical Devices in New Zealand - Faunce, Thomas A; Johnston, Kellie; Bambrick, Hilary (Victoria University of Wellington Law Review, 2006)
Australia and New Zealand have agreed in principle to the creation of a single agency for the regulation of pharmaceuticals and other therapeutic products in a trans-Tasman market. The Australia New Zealand Therapeutic Products Authority (ANZTPA) is being developed to replace both the Australian Therapeutic Goods Administration (TGA) and the New Zealand Medicines and Medical Devices Safety Authority (Medsafe). This article explores the possibility that the ANZTPA, by inheriting significant obligations imposed on the TGA under the Australia-United States Free Trade Agreement (AUSFTA), may significantly impact upon the regulation of medicines and medical devices (as well as blood products) in New Zealand. It explores the related legal obligations and their likely consequences for New Zealand: particularly quality, safety, efficacy and cost-effectiveness evaluation processes in this area, such as those of the New Zealand Pharmaceutical Management Agency (Pharmac).